2019
DOI: 10.1093/glycob/cwz079
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense and inactivating variant of ST3GAL3 in two infant siblings suffering severe epilepsy and expressing circulating CA19.9

Abstract: Three missense variants of ST3GAL3 are known to be responsible for a congenital disorder of glycosylation determining a neurodevelopmental disorder (intellectual disability/epileptic encephalopathy). Here we report a novel nonsense variant, p.Y220*, in two dichorionic infant twins presenting a picture of epileptic encephalopathy with impaired neuromotor development. Upon expression in HEK-293T cells, the variant appears totally devoid of enzymatic activity in vitro, apparently accumulated with respect to the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(69 citation statements)
references
References 34 publications
3
65
1
Order By: Relevance
“…Decreased ganglioside levels, especially GM1 and GD1a were found in the cerebrospinal fluid (CSF) of a small number of patients with West syndrome (Izumi et al, 1993), an infantile epilepsy disorder caused by a variety of genetic, metabolic and developmental factors (D'Alonzo et al, 2018). More recently, loss-of-function mutations in ST3GAL3 -one of the two sialyltransferases involved in the synthesis of GD1a and GT1b (Sturgill et al, 2012; Figure 1) -were found in patients with West syndrome (Edvardson et al, 2013) and in two siblings with epileptic encephalopathy (Indellicato et al, 2019). In animal models, ST3GAL3 catalyses the sialylation of glycoproteins in addition to glycolipids (Sturgill et al, 2012).…”
Section: Epilepsymentioning
confidence: 99%
“…Decreased ganglioside levels, especially GM1 and GD1a were found in the cerebrospinal fluid (CSF) of a small number of patients with West syndrome (Izumi et al, 1993), an infantile epilepsy disorder caused by a variety of genetic, metabolic and developmental factors (D'Alonzo et al, 2018). More recently, loss-of-function mutations in ST3GAL3 -one of the two sialyltransferases involved in the synthesis of GD1a and GT1b (Sturgill et al, 2012; Figure 1) -were found in patients with West syndrome (Edvardson et al, 2013) and in two siblings with epileptic encephalopathy (Indellicato et al, 2019). In animal models, ST3GAL3 catalyses the sialylation of glycoproteins in addition to glycolipids (Sturgill et al, 2012).…”
Section: Epilepsymentioning
confidence: 99%
“…Detection of CA19.9 in the serum or other fluids or tissue homogenates is easily performed by a sandwich Enzyme-linked immunosorbent assay (ELISA) [44] using immobilized and labeled anti-CA19.9 antibody as the capture and detection antibody, respectively. We have set a similar procedure for Lea and Leb using the corresponding antibodies purified from available hybridomas (anti-Lea 151-6-A7-9, ATCC HB 8324, and anti-Leb 130-3-F7-5, ATCC HB 8326) and screened up to 20 sera collected from healthy volunteers, obtaining a range of values spanning from unmeasurable to an arbitrary maximum level, which was assumed as a reference putative normal range for each antigen.…”
Section: A Proposed Model Of Circulating Ca199 and Type 1 Chain Lewimentioning
confidence: 99%
“…However, the exclusive role of ST3GAL3 has been definitely ruled out very recently in a study of two young children harboring a recessive non-sense mutation of the gene. They carry a totally inactive ST3GAL3 variant but do express circulating CA19.9 at high levels, according to their age [44]. This indicates that multiple ST3GALs independently contribute to synthesize the epitope.…”
Section: Introductionmentioning
confidence: 99%
“…The first case was reported in 1974, when an infant presented with severe motor impairment and persistent seizures culminating in death by 3.5 months of age [73]. A variant of GM3 synthase was also found in a patient that suffered from severe auditory, visual, motor and cognitive impairments, as well as respiratory chain dysfunction [74]. Due to the absence of ST3Gal V activity, a post-mortem examination of the patient's brain revealed a complete absence of complex gangliosides.…”
Section: Genetic Defects Of Glycosphingolipid Biosynthesismentioning
confidence: 99%
“…In a patient with West syndrome (ST3Gal III-CDG), an illness characterized by epileptic spasms (ranging in severity), abnormal brain waves and intellectual disability [75], the α2,3-sialyltransferase III was found to be deficient, thus decreasing α2-3sialylation of Gal linked to GalNAc in GD1a, GT1b and GQ1c, which causes an accumulation of GM1. Missense variants of ST3Gal III have also been associated with epileptic encephalopathy and impaired neuromotor development in an infant [74]. In cortical neurons derived from induced pluripotent stem cells isolated from patients, a missense variant of ST3Gal III was associated with altered lectin binding patterns and enhanced adherence to poly-L-ornithine/laminin-coated surfaces [76].…”
Section: Genetic Defects Of Glycosphingolipid Biosynthesismentioning
confidence: 99%